Transcriptional Analysis of Infection With Early or Late Isolates From the 2013–2016 West Africa Ebola Virus Epidemic Does Not Suggest Attenuated Pathogenicity as a Result of Genetic Variation - Maroney, Kevin J.; Pinski, Amanda N.; Marzi, Andrea; Messaoudi, Ilhem (Frontiers in Microbiology, 2021)
The 2013-2016 West Africa Ebola virus (EBOV) epidemic caused by the EBOV-Makona isolate is the largest and longest recorded to date. It incurred over 28,000 infections and ~11,000 deaths. Early in this epidemic, several mutations in viral glycoprotein (A82V), nucleoprotein (R111C) and polymerase L (D759G) emerged and stabilized. In vitro studies of these new EBOV-Makona isolates showed enhanced fitness and viral replication capacity. However, in vivo studies in mice and rhesus macaques did not provide any evidence of enhanced viral fitness or shedding. Infection with late isolates carrying or early isolates lacking (early) these mutations resulted in uniformaly lethal disease in nonhuman primates, albeit with slightly delayed kinetics with late isolates. The recent report of a possible reemergence of EBOV from a persistent infection in a survivor of the epidemic highlights the urgency for understanding the impact of genetic variation on EBOV pathogenesis. However, potential molecular differences in host responses remain unknown. To address this gap in knowledge, we conducted the first comparative analysis of the host responses to lethal infection with EBOV-Mayinga and -Makona isolates using bivariate, longitudinal, regression and discrimination transcriptomic analyses. Our analysis shows a conserved core of differentially expressed genes involved in antiviral defense, immune cell activation, and inflammatory processes in response to EBOV-Makona and -Mayinga infections. Additionally, EBOV-Makona and EBOV-Mayinga infections could be discriminated based on the expression pattern of a small subset of genes. Transcriptional responses to EBOV-Makona isolates that emerged later during the epidemic, specifically those from Mali and Liberia, lacked signatures of profound lymphopenia and excessive inflammation seen following infection with EBOV-Mayinga and early EBOV-Makona isolate C07. Overall, these findings provide novel insight into the mechanisms underlying the lower case fatality rate observed with EBOV-Makona compared to EBOV-Mayinga.